The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12913-022-08018-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma, substance use and self-medication in night-shift healthcare workers: a qualitative study

Abstract: Background Many risk factors related to altered circadian rhythms impact the health of night-shift hospital workers (NSHW), resulting in mental and somatic disorders. Easy access to psychoactive substances (PS) may facilitate addictive behaviors in NSHW. They are also exposed to a stressful work environment, which may further affect sleep quality. This study aimed to explore the link between sleep deprivation, work-related psychosocial stress and psychoactive substance use as a self-medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It is well established that the stigma associated with AUD, is one of the most prominent barriers to treatment-seeking [ 17 20 ]. Previous studies have mainly focused on barriers to treatment and there is therefore a need to also investigate what individuals would potentially do if they developed AUD, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the stigma associated with AUD, is one of the most prominent barriers to treatment-seeking [ 17 20 ]. Previous studies have mainly focused on barriers to treatment and there is therefore a need to also investigate what individuals would potentially do if they developed AUD, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses use or abuse different types of substances, like non-prescribed medications, alcohol, khat or cigarette to alleviate the stress associated with shift work [ 22 , 41 ]. Shiftwork by itself was associated with nurses’ use/abuse of substances [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be because of sleep disorders experienced by healthcare workers caused by night shift work. 24 Many studies have demonstrated a strong association between night shift work and sleep disorders. These disorders are related to the alteration of circadian rhythms and have been identified as a potential cause of certain addictive behaviors and psychological distress.…”
Section: Discussionmentioning
confidence: 99%